A Comparative Study Between the Use of Efficacy of Topical Sucralfate vs 5% Povidone Iodine in Chronic Lower Limb Non-Healing Ulcers - Vivek, Modiem Ram; Elangovan, Ram Prasath; Prabakar, A. (Journal of Neonatal Surgery, 2025)
Objective: This study aimed to compare the efficacy of topical sucralfate versus 5% povidone-iodine in treating chronic lower limb non-healing ulcers, focusing on granulation tissue formation, ulcer size reduction, healing time, infection rates, and patient satisfaction. Methods: A retrospective comparative cohort study was conducted at Chettinad Hospital and Research Institute, Chennai, from January 2024 to December 2024. Sixty patients with chronic lower limb ulcers were divided into two groups: Group A (n=30) treated with 5% povidone-iodine dressings and Group B (n=30) treated with topical sucralfate dressings. Dressings were changed every alternate day, and patients were followed up for three weeks. Outcome measures included granulation tissue formation, ulcer surface area reduction, healing time, infection rates, and patient satisfaction. Data were analyzed using SPSS version 26.0, with statistical significance set at p<0.05. Results: The sucralfate group showed significantly better outcomes compared to the povidone-iodine group. Granulation tissue formation was "Good" or "Excellent" in 60% of sucralfate-treated patients versus 26.7% in the povidone-iodine group (p<0.001). The mean reduction in ulcer surface area was 7.8 cm² in the sucralfate group compared to 4.2 cm² in the povidone-iodine group (p<0.01). Healing time was significantly shorter in the sucralfate group (28.7 days vs. 42.5 days, p<0.001). Infection rates were lower in the sucralfate group (10% vs. 26.7%, p<0.05), and patient satisfaction was higher (80% vs. 50%, p<0.05). Conclusion: Topical sucralfate demonstrated superior efficacy in promoting wound healing, reducing infection rates, and improving patient satisfaction compared to 5% povidone-iodine. These findings suggest that sucralfate is a viable alternative for managing chronic lower limb ulcers, potentially improving clinical outcomes and reducing healthcare costs. Further prospective studies are recommended to validate these results